New works of Russian Islam history and culture research - Dashnyam, Zolboo (Journal of International Studies, 2022)
This abstract article is devoted to a review of the content of an important, new collective work of Russian Islamic scholars (authors: A.K. Alikberov, V.O. Bobrovnikov, A.K. Bustanov) “Russian Islam Essays on History and Culture” (2nd ed. , corrected and supplemented, Strategic Vision Group "Russia-Islamic World" - M.: IV RAS, 2018. - 456 p.). The content of the preface, introduction, twelve chapters and the conclusion of the work is described in detail in the article in abstract form. The author of the article emphasizes the novelty, research significance and value of work, the importance and validity of the theoretical and methodological approach of the authors to the problem of the history and culture of Islam in the Russian Federation.